Navigating the nexus of type 2 diabetes mellitus and breast cancer: a comprehensive review of co-occurrence - Saroosh, Rabiya; Ahmad, Nazir; Israr, Beenish; Arif, Sana; Itrat, Nizwa; Ahmad, Abdul Momin Rizwan (Frontiers in Oncology, 2025)
The co-occurrence of type 2 diabetes mellitus and breast cancer has received considerable attention due to their global prevalence and shared metabolic pathways, greatly affecting quality of life and life expectancy, especially in women. Epidemiological evidence indicates that women with type 2 diabetes mellitus have a 20-30% higher risk of developing breast cancer than women without type 2 diabetes mellitus. This review was conducted through a comprehensive and structured literature search to identify relevant peer-reviewed studies examining the relationship between type 2 diabetes mellitus and breast cancer. To ensure the quality and relevance of the included literature, only studies published in English were considered. The focus was on literature addressing pathological mechanisms, epidemiological data, and shared risk factors contributing to the coexistence of these conditions. Preference was given to recent publications, including systematic reviews, meta-analyses, and high-quality original research articles. The primary databases searched included PubMed, Scopus, Web of Science, and Google Scholar. The increased risk of breast cancer among type 2 diabetic patients is largely attributed to shared risk factors such as obesity, hyperglycemia, dietary patterns, physical inactivity, age, hormonal imbalances, and genetic predispositions, all of which contribute to the coexistence of these conditions. Chronic inflammation, hyperinsulinemia, and persistent hyperglycemia, together with dysregulation of adipokine and estrogen signaling, create a carcinogenic environment that facilitates the development of breast cancer in type 2 diabetic patients. This review emphasizes the urgent need for a multidisciplinary approach to prevention and treatment. Effective intervention strategies can reduce the dual burden of these diseases, resulting in better patient outcomes and improved quality of life.